Diction and Discourse Dynamics: A Critical Analysis of Roy Suryo's Opinion on The Broadcasting Law - Habibullah, Bukran; Efendi, Anwar; Kamarudin, Samsul (Indonesian Scientific Publication, 2025)
The purpose of this study is to examine more deeply the text, along with the ideological and social contexts underlying the opinion piece. This research employs a qualitative approach, using Norman Fairclough’s theoretical perspective. The findings reveal that the textual dimension contains both explicit and implicit linguistic features, indicating strong semantic content. The sentences used in the text can be categorized into two main types: declarative and interrogative sentences. In the dimension of discursive practice, the opinion piece aims to build public collective awareness so that citizens are actively involved in overseeing public policies—particularly those concerning the right to information, freedom of expression, and freedom of the press. In terms of sociocultural analysis, there is an institutional involvement of the House of Representatives (DPR) and the Indonesian Broadcasting Commission (KPI) in “intervening” in matters related to journalistic content. This raises serious concern, as a healthy, free, and responsible press is being “silenced.” If press freedom is curtailed, one of the key pillars of democracy—the press’s role in providing checks and balances—will be significantly undermined.